Phylogeography of Parasyncalathium souliei (Asteraceae) and Its Potential Application in Delimiting Phylogeoregions in the Qinghai-Tibet Plateau (QTP)-Hengduan Mountains (HDM) Hotspot - Lin, Nan; Deng, Tao; Moore, Michael J.; Sun, Yanxia; Huang, Xianhan; Sun, Wenguang; Luo, Dong; Wang, Hengchang; Zhang, Jianwen; Sun, Hang (Frontiers in Genetics, 2018)
Biogeographic regionalization can help to better understand diversity in biogeography, conservation, and macroecology. Historical regionalization schemes typically focus on species distributions, often rarely considering the rich context that phylogeographic information can provide. We investigated whether phylogeographic data could help to delineate floristic regions in the Qinghai-Tibet Plateau (QTP)-Hengduan Mountains (HDM) region by analyzing phylogeographic structure in the herb Parasyncalathium souliei (Asteraceae). We sequenced the plastid psbA-trnH and trnL-rpl32 spacer regions for 417 individuals in 36 populations across the geographic range of the species. To estimate the phylogeographic history of this species, a series of population genetic, phylogenetic, molecular dating, and haplotype network analyses were conducted, as were tested for historical demographic expansions. Using occurrence data, species distribution modeling was used to estimate geographic distributions at three time points: the present, the Mid-Holocene and the Last Glacial Maximum. Significant phylogeographic structure was evident (NST > GST; P < 0.05) among the 37 haplotypes detected. Four major haplogroups were identified based on phylogenetic analyses. Private haplotypes were restricted to geographically distinct regions that generally corresponded to previously identified biogeographic subregions within the QTP-HDM region. Our results imply Pliocene-Pleistocene diversification of P. souliei and suggest that the species may have been geographically widespread early in its history. This study may provide valuable evidence for phylogeographic regionalization using chloroplast genetic data in a common, widespread endemic species from the QTP-HDM.